Experimental study on mechanical and corrosion characteristics of nab alloy with the addition of chromium. (2018) - Parameswaran, P.; Godwin Antony, A.; Dinesh, S.; Radhakrishnan, K.
Abstract: The issue of corrosion is a major problem on equipment failure and damage in industrial that would affect the safety and efficiency of the equipment. Especially, materials used in marine environments have to withstand corrosion and need more hardness to withstand corrosion. Nickel–aluminum bronze (NAB) alloys show good corrosion resistance under marine conditions. Therefore material requirements to withstand such a high corrosive environment are most important. Along with these, cost effectiveness also considered in the usage of material. Many papers gives the corrosion resistance of behavior of NAB alloys in sea water or 3.5M NaCl solution in detail manner. But the alternate material to NAB is not studied as copper is the material shows very high corrosion resistance in sea water. In order to enhance the properties of NAB alloy, chromium is added additionally and excluding iron, manganese, bronze, etc of the NAB alloy. This paper will be focusing on the influence of chromium addition to the aluminum nickel alloy in the corrosion resistance properties and hardness. Chromium is added in 4%, 8% and 12% through powder metallurgy route. The specimen prepared for the corrosion testing by sintering and hot – extrusion. The electro-chemical corrosion test was carried out in Potentiostat in order to find out the corrosion properties of the alloys. The corrosion properties were increased than the available alloy composition of ASTM B505M – 14. Further, the micro-vicker's is done which shows that the micro-hardness also has got increased due to the addition of chromium. The main aim of the paper is to find an alternate material which withstands high corrosive environment especially in salt water and also high strength.